Numerical Analysis for Thermal Design of a Paraboloidal Solar Concentrating Collector - Hasnat, A; Ahmed, P; Rahman, M; Khan, KA (International Journal of Natural Sciences, 2011)
A paraboloidal solar concentrating collector in a non-planar configuration using reflecting materials of reflectance is 0.7 has been thermally designed and developed and at a 1metre focal distance in conjunction with a reverse flat plate absorber with black board paint (both selective and non selective coating) theoretically. To study optical and thermal performance tests like stagnation temperature (Tps), water temperature (Tw), plate temperature (Tp), thermal efficiency test (Xc), optical efficiency test (Xo), Heat transfer coefficient from surface to water (U), geometrical concentration ratio (C) and overall heat loss coefficient (U2) has been studied. The concentrator is placed such that all incident parallel rays of light intercepted by the concentrator aperture are reflected to a common focus. In this case the concentrator parabolic in shape. This communication presents the thermal design analysis of a CR- system. The results of some typical numerical calculations are shown graphically and their significance is discussed. Key words: Concentrating collector; mass flow rate; solar and thermal conversion. DOI: http://dx.doi.org/10.3329/ijns.v1i3.8824 International Journal of Natural Sciences (2011), 1(3):68-74